ANALISA TINGKAT BAHAYA EROSI PADA SUB DAS LESTI KABUPATEN MALANG MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS - Ernawan Setyono; Bangkit Prasetyo (Media Teknik Sipil, 2012)
Ernawan Setyono1& Bangkit Prasetyo21&2Fakultas Teknik Jurusan Teknik Sipil Universitas Muhammadiyah MalangAlamat Korespondensi : Jl. Raya Tlogomas, No.246 Malangemail :ernawan@umm.ac.id , Telp 03419591639ABSTRACTSub DAS Lesti is a part of Brantas watershed that located at upstream section and a sub DASpriority. That has 61.491,02 ha of water catchment areas. Hydrological processes that occur in awatershed is closely related to erosion. The alteration of land use and watershed management is oneof the factors causing soil damage, accelerate the erosion rate, and cause erosion. Based on thecondition of that case, this study analyzes about how much the erosion rate, the amount of erosion,and to estimate the level of erosion that will occur.MUSLE method is one of the methods used to determine the magnitude of the erosion rate,that use an approach of runoff factor. Geographic Information Systems (GIS) used for the managementand data processing. Geographic Information Systems is a spatially information technology thatgenerate digital data which can gives the area characteristics, and illustrates the potential of soildamage.The level of erosion hazard on Sub DAS Lesti for weight categories reach 31.421% of thearea, while another erosion rate is Medium 24.146%, Lightweight 22.151%, Very Heavy 16.123%,and Very Light 6.159%.